Identifying Prospective Biology Teachers’ Digital Literacy Competence at Cenderawasih University - Nurbaya Nurbaya (Postgraduate, University of Mataram, 2023)
Nowadays, integrating ICT into learning and teaching practice is a challenge faced in the education world. The current educational system requires teachers to master digital literacy competence. The purpose of the present study was to identify the digital literacy competence of prospective biology teachers at Cenderawasih University. A descriptive and quantitative approach, with the survey model, was applied in this paper. A random sampling technique was used with 71 student teachers as data informants. Data were collected from questionnaire items and documentation. Overall, prospective biology teachers’ digital literacy competence was at a high level. Student teachers scored highest in information skills, rated at very high criteria, the second and third areas, namely communication and content-creation, were at high criteria. The lowest values were indicated in safety and problem-solving